Prolactinomas may have unusual presentations resulting from massive extrasellar tumor extension - Marise Ribeiro de Sousa Berriel; Giovanna Aparecida Balarini Lima; Alessandro Severo Alves de Melo; Maria Laura Vasconcelos dos Santos; Hassan Rahhal; Giselle Fernandes Taboada (Arquivos de Neuro-Psiquiatria)
ABSTRACT The purpose of this case series is to report eight patients with giant prolactinomas emphasizing presentations and a treatment complication. The study group included six men and two women. The median age was 29 years (18–54 years); median serum prolactin level was 4,562 ng/ml (1,543–18,690 ng/ml); three patients (37.5%) had panhypopituitarism; median tumor diameter was 50 mm (41–60 mm). Five patients (62.5%) had visual field defects and three had improvement during treatment; six patients (75%) reached prolactin normalization, with a median time of 10.5 months (7–84 months) and median dose of 2.0 mg/week (1.0 to 3.0 mg/week). One patient presented as a true incidentaloma. One patient presented a cerebrospinal fluid leakage during medical treatment and refused surgery, however this resolved with conservative measures. This case series illustrate a rare subtype of macroprolactinomas, the importance of considering unusual presentations at the diagnosis, the effectiveness of pharmacological treatment and its possible complications.